2018
DOI: 10.3390/polym10040457
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Aluminosilicate- and Aluminum Oxide-Filled Thermosets for Injection Molding: Effect of Filler Content, Filler Size and Filler Geometry

Abstract: In this study, epoxy molding compounds (EMCs) with aluminosilicate (AlS) and aluminum oxide (AlO) were fabricated as fillers by a twin-screw-extruder (TSE) and shaped to plate samples using injection molding. AlS and AlO, electrical insulating mineral materials, were used as fillers to improve the thermal conductivity (λ c ) of composites. Composites with different filler particle sizes, filler contents and filler geometry were fabricated and the influence of these variables on the λ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…The highest thermal conductivity was obtained for the 007sst45 sample with 63% relative increase in relation to the reference sample filled with silica. The received thermal conductivity for composites with fillers 007sst45 and 010est45 are improved in relation to similar samples presented in the literature , what may indicate that processing method selected herein was more effective for heat paths formation.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The highest thermal conductivity was obtained for the 007sst45 sample with 63% relative increase in relation to the reference sample filled with silica. The received thermal conductivity for composites with fillers 007sst45 and 010est45 are improved in relation to similar samples presented in the literature , what may indicate that processing method selected herein was more effective for heat paths formation.…”
Section: Resultssupporting
confidence: 73%
“…Moreover, filler surface treatment was emphasized as an essential step for the appropriate distribution of a filler in the polymer matrix and enhanced bonding between components . It is also worth to notice paper presented by Zhao et al where thermal conductivity of the Silatherm‐epoxy resin injection molded composites were examined, and it was found that thermal conduction can be successfully improved by Silatherm incorporation. However, in order to assess if the material is suitable as an electrical insulation, it is necessary to investigate also dielectric and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to manipulating polymer chain alignment to form specic orientations [7][8][9] and yield high crystallinity 10,11 in the matrix to obtain high thermal conductivity, doping llers with high thermal conductivity into polymers is a simple and effective way to improve the thermal conductivity of composites. However, the type, [12][13][14][15] dimensions, [16][17][18][19] size 20,21 and concentration 22,23 of the ller are factors that play signicant roles in the thermal conductivity of composites. In addition to the above factors, two other important factors are the ller arrangement in the polymer matrix, [24][25][26][27] which forms thermal conduction pathways, and the interfacial thermal resistance caused by the poor dispersion and weak interaction of the ller.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the thermal properties, high thermal conductivity fillers, such as aluminum oxide (Al 2 O 3 ) [ 14 , 15 ], boron nitride (BN) [ 16 , 17 , 18 , 19 ], silicon nitride (Si 3 N 4 ) [ 20 , 21 ], and aluminum nitride (AlN) [ 22 , 23 ] etc. are added into the polymer matrices.…”
Section: Introductionmentioning
confidence: 99%
“…are added into the polymer matrices. However, a number of studies indicate that higher thermal conductivity or excellent dielectric property is always accompanied by high filler content [ 24 , 25 ] such as high thermal conductivity filler Al 2 O 3 [ 14 , 15 , 26 ] ( f thermal-conductive filler > 50%) or high dielectric filler [ 4 ] such as BaTiO 3 (BT) ceramic [ 24 , 25 , 27 ] ( f dielectric filler > 50%) to achieve the corresponding properties, and over load of various fillers ( f fillers > 50%) will greatly reduce processability and mechanical properties of the composite [ 21 , 28 , 29 , 30 ], and limited its applications scope. As a result, the overall thermal conductivity, dielectric properties, and mechanical properties etc.…”
Section: Introductionmentioning
confidence: 99%